Tuberculous pyloric stenosis; successful medical therapy may obviate surgery - Badawi, Muhammad; Yousef, Jamshed; Nasser, Wafa; Younis, Muhammad (Ibnosina Journal of Medicine and Biomedical Sciences, 2012)
Gastroduodenal involvement occurs in only 0.3 to 2.3% of patients with tuberculosis (TB). Clinically, it may resemble peptic ulcer disease or malignancy. We present a 36 year old man with gastric outlet obstruction proven to be pyloric stricture due to primary pyloric tuberculosis. Diagnosis was established endoscopically and patient was successfully managed by standard anti-tuberculous therapy. Although rare, tuberculous involvement of the stomach should be considered in the differential diagnosis of gastric outlet obstruction especially in regions where tuberculosis is endemic. This case also emphasizes that medical management with anti-TB medications can be tried solely as the first line therapy for strictured pyloric stenosis. However, surgical intervention is required more often than none in cases where gastrointestinal obstruction is the main clinical problem.
Keywords: Tuberculosis; Pyloric Stenosis; Gastric Tuberculosis